The Effect of Job Satisfaction and Organizational Culture on Organizational Citizenship Behavior with Organizational Commitment as a Mediation Variable at Bank Rakyat Indonesia - Puspitasari, Ni Komang Dian Ratih; Mahyuni, Luh Putu (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to determine the effect of job satisfaction and organizational culture on organizational citizenship behavior with organizational commitment as a mediating variable at Bank Rakyat Indonesia (BRI) Bo Denpasar Gajah Mada. This type of research is quantitative using secondary data. The population in this study were all employes of BRI Denpasar Gajah Masa. The sample in this study was 260 respondents. The questionnaire data collection technique used Google form. Data processing for descriptive analysis used SPSS statistical application software and was analyzed using SEM with the help of Partial Least Squares (PLS) software. Job satisfaction and organizational culture have a positive and significant influence on organizational citizenship behavior and organizational commitment and organizational culture. has a positive and significant influence on organizational citizenship behavior and organizational commitment. Organizational commitment has a positive and significant influence on organizational citizenship behavior. employee loyalty of PT Bank Rakyat Indonesia (Persero) Tbk BO Denpasar Gajah Mada is very strong Towards customers and other employees, employees are also very satisfied with their performance results, the company culture is very strong and employees are very committed to the targets given by the company